Development of Novel Genomic Blood Biomarkers for Neurodegenerative Diseases - Borovecki, Fran; Habek, Mario (CNS & Neurological Disorders - Drug Targets, 2010)
Genomic blood biomarkers hold great promise for development of novel clinical and therapeutic approaches in patients with neurodegenerative diseases. Such biomarkers could prove invaluable in early disease diagnosis, monitoring of disease progression, or assessment of response to therapy. More importantly, they could be helpful in search for disease-modifying new therapies which are very much needed in modern approaches to treatment of neurodegenerative diseases, serving as surrogate endpoints in clinical trials. However, when performing expression profiling experiments aimed at discovery of new biomarker genes, standard operating procedures regarding sample collection, microarray methodology, and statistical analysis need to be fully developed and strictly adhered to. Several studies performed on patients with multiple sclerosis, Huntington's, Parkinson's and Alzheimer's disease offer promise that such approaches might prove useful in clinical practice. Crucial for successful application of any genomic biomarker will be confirmation in multiple independent patient cohorts and correlation of the improvement in biomarker endpoint with clinical improvement in longitudinal patient studies.
Keywords: (akynesia)